ENGLISH CURRICULUM DEVELOPMENT OF ELEMENTARY SCHOOL AT SDNU BANAT BANIN LAMONGAN - Sholeh, Agus; Anam, Mukhtarul (E-Link Journal, 2020)
In this modern era, learning English is a must for every human. therefore, learning English at early level is better done. This time, it is determined that English subjects in elementary schools are local content group subjects whose status is as elective subjects, so the material is determined by each school. This research was using Qualitative descriptive. It is about An Analysis English Curriculum Development at SDNU Banat Banin lamongan. The Subject of the research was the teacher and the 5-grade at SDNU Banat Banin Lamongan in the academic year of 2019/2020. There are 30 students. The finding of the research, the curriculum applied at SDNU Banat Banin Lamongan was the 2013 curriculum and the researcher found four aspects that are done by SDNU Banat Banin Lamongan as curriculum development in learning English starting from the purpose of curriculum development, learning material, learning methods, and learning evaluation and the material presented in fifth grade in SDNU Banat Banin Lamongan is grammar, translating text, making sentences, and knowing the difference in the meaning of a word and once every week on Wednesday there is a habit of Speaking English .Â Â